Magnetoimpedância em multicamadas de Ni81Fe19/Cu com a corrente de sonda perpendicular ao plano do filme - Callegari, Gustavo Luiz (2006)
In this work the behavior of the magnetoimpedance (MI) in ferromagnetic multilayered (Ni81Fe19/Cu) produced by magnetron sputtering was studied. In all measurements, the probe current was applied perpendicularly to the film surface. The MI measurements were performed in the frequency range 100kHz - 1.8GHz with an HP-4396B impedance analyzer and a specially designed sample holder. Magnetoimpedance ratios of 150% were obtained in some of the studied samples.